Audit of fresh frozen plasma usage, prospective study: a report from department of immunohematology and transfusion medicine, government medical college Jammu, Jammu and Kashmir, India - Shah, Saadat Nazir; Sidhu, Meena; Gupta, Vidushi (International Journal of Research in Medical Sciences, 2020)
Background: Fresh frozen plasma is commonly used in tertiary care hospitals. These are used to manage conditions such as coagulation derangements. Unnecessary use of fresh frozen plasma (FFP) is known to increase the risk of side effects in plasma transfusing patients like anaphylaxis, transfusion related acute lung injury (TRALI) and risk of transfusion transmitted infections etc. So judicious use of plasma is extremely important where its benefits outweigh its potential risks. Methods: Prospective observational study conducted over a period of six month. The following data were collected; provisional clinical diagnosis, indication of FFP’S, coagulation profile and gender of the patients. We evaluated all FFP transfusions, classified them as appropriate or inappropriate according to fresh frozen plasma transfusion guidelines of Directorate general of health services (DGHS). Results: A total of 808 FFP units were issued (474 units to males and 334 units to females) over a period of 6 months. Out of these, 15% (122 units) of FFP’s were issued to intensive care unit (ICU) patients, 12.87% (104 units) to paediatrics ward, 12.25% (99 units) to emergency ward which include patients with upper GI bleed and lower GI bleed , 6.8% (55 units) to obstetrics patients, 6.18% (50 units) to orthopaedics, 4.45% (36 units) to road traffic accident patients, 4.20% (34 units) to Hepatic failure patients, 3.09% (25 units) to Cardiothoracic and vascular surgery (CTVS), 2.97% (24 units) to oncology patients, 2.47% (20 units) to snake bite patients, 1.23 % (10 units) to dengue patients, 1.11% (9 units) to Haemophilia patients, 27.38% units were issued to the patients were indication for FFP transfusion was not known. Conclusions: study showed that 66.44% were appropriate and 33.56% were inappropriate use of FFP’s in patients. This highlights the pitfalls in use of FFP among clinicians and for that matter there is need of awareness and understanding the transfusion medicine by clinicians.